Disability Benefit Take-Up and Local Labor Market Conditions - Charles, Kerwin Kofi; Li, Yiming; Stephens, Melvin (The Review of Economics and Statistics, 2018)
Exploiting county-level variation in oil-producing areas from shocks to world oil and gas prices, we study how local labor market conditions affect disability take-up. We extend well-known previous work using a similar research design by analyzing a different price shock; a larger, more representative set of labor markets; and a more recent period marked by skyrocketing disability payments. Our estimated elasticity for SSDI payments with respect to earnings of −0.29 is surprisingly similar to earlier findings. Our preferred SSI elasticity estimate of −0.16 is smaller than previous findings, but we show that SSI programmatic changes explain most of the difference.